The Legal Conundrums of the Metaverse - Safari Kasiyanto; Mustafa R. Kilinc (Bank Indonesia, 2022)
The metaverse gained its momentum after a CEO of the biggest social media made a statement that it would be the next big thing after the Internet. Although there is no single, agreed definition of the metaverse, the common understanding of the metaverse is that the concept combines IoT, AR, VR, XR, and 3D technologies. It is also called the Web 3.0. The market capital and the economic potential of the metaverse are enormous. The market cap was calculated around USD14.8 trillion in October 2021 while the economic potential ranged from USD3,75 trillion to USD12.5 trillion. Hence, it is of importance to discuss the legal aspects of the metaverse. This article is the first to elaborate the legal conundrums of the metaverse in a more proper manner. It includes discussion on the property law and intellectual property law, and whether the time has come to have “a virtual property law”. It also discusses some other legal aspects such as privacy and data protection, contract law and smart contracts, cybersecurity and cyberattacks, monetary and payment systems laws, and regulation of virtual assets (including securities and commodities laws), tax law, anti-money laundering and KYC, and criminal law. To give a more comprehensive view, some governance and ethical issues of the metaverse are also touched upon.